USING NARRATIVE INQUIRY TO EXAMINE TEACHERS' IDENTITY VIA FACEBOOK NARRATIVES - Khoi, Mai Ngoc; Long, Tran Thi (VNU Journal of Foreign Studies, 2021)
Identity is the result of one's personality, upbringing, learning and working experience. This article presents the results of a research on the personal identity of a lecturer teaching English at a university in Vietnam. The article analyzes the teacher's shared narratives on Facebook about his life and teaching experiences. In-depth interviews were conducted over a one-year period following narrative inquiry procedure. The paper shows the complexity of the participant's four intertwined identities as well as the potential of Facebook as an online platform to share and reflect on personal experiences, thereby allowing readers to engage in a dual process of identification and negotiation of meanings ​​in identity formation. Social networks have the potential to mitigate the isolation of teachers in their pursuit of professional development activities and to promote the formation and development of professional communities.